2018
DOI: 10.1021/acs.jpca.8b01329
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Tantalum Carbide Cluster Anions TaCn (n = 1–4) with Dinitrogen

Abstract: Dinitrogen activation/fixation is one of the most important and challenging subjects in synthetic as well as theoretical chemistry. In this study, the adsorption reactions of N onto TaC ( n = 1-4) cluster anions have been investigated by means of mass spectrometry in conjunction with density functional theory calculations. Following the experimental results that only TaC was observed to adsorb N, theoretical calculations predicted that the TaC reaction system (TaC + N → TaCN) has a negligible barrier on the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…Photoionization efficiency spectroscopy and theoretical calculations of Ta 3 C 1–3 , Ta 4 C 1–4 , Ta 5 C 0–6 , and Ta 1–6 C 1–7 clusters showed that the C 2 units disappeared in the large-sized clusters with increasing number of Ta atoms. Electron affinity of TaC – was measured to be 1.928 ± 0.056 eV by anion photoelectron spectroscopy . Mass spectrometry and photoelectron imaging spectroscopy combined with quantum chemical calculations found that N 2 and CH 4 can be activated by TaC 4 – and Ta 2 C 4 – . Far-infrared spectra of the Ta 5 12 C 3 cluster confirmed its first electronic excitation state to be 458 cm –1 . Anion photoelectron spectroscopy and theoretical calculations of Ta 4 C n – ( n = 0–4) clusters showed that the Ta–Ta bonds were gradually replaced by Ta–C bonds with increasing number of carbon atoms .…”
Section: Introductionsupporting
confidence: 81%
“…Photoionization efficiency spectroscopy and theoretical calculations of Ta 3 C 1–3 , Ta 4 C 1–4 , Ta 5 C 0–6 , and Ta 1–6 C 1–7 clusters showed that the C 2 units disappeared in the large-sized clusters with increasing number of Ta atoms. Electron affinity of TaC – was measured to be 1.928 ± 0.056 eV by anion photoelectron spectroscopy . Mass spectrometry and photoelectron imaging spectroscopy combined with quantum chemical calculations found that N 2 and CH 4 can be activated by TaC 4 – and Ta 2 C 4 – . Far-infrared spectra of the Ta 5 12 C 3 cluster confirmed its first electronic excitation state to be 458 cm –1 . Anion photoelectron spectroscopy and theoretical calculations of Ta 4 C n – ( n = 0–4) clusters showed that the Ta–Ta bonds were gradually replaced by Ta–C bonds with increasing number of carbon atoms .…”
Section: Introductionsupporting
confidence: 81%
“…It is clear that the local maxima ( V s,max ) are always located near metal atoms, and the values of V s,max near dopant V atoms are larger than those near Mo atoms. Larger positive electrostatic potentials may facilitate the initial approach of the nonpolar N 2 molecule to the clusters [15c] . Therefore, we paid more attention to the adsorption of N 2 on metal atoms in Mo 6 S 8 q _V x , especially on V atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Gas-phase clusters are ideal models for simulating the active sites of related condensed phase systems, which can be used to understand the bond activation process under isolated and well-controlled conditions at a strictly molecular level [25][26][27][28], and is suitable to provide insights into the mechanisms of SAC and SCC [29]. A large number of experiments and theoretical work have explored the mechanism of N 2 activation by gas-phase clusters, mainly focusing on metal clusters [30][31][32][33][34][35], metal carbide clusters [36,37], and metal nitride clusters [38,39]. Coordination modes of N 2 on supporting atoms were found critical for N 2 activation.…”
Section: Introductionmentioning
confidence: 99%